The midwifery of power? Reflections on the development of professional social work in Western Australia - Crawford, Frances; Leitmann, Sabina (Routledge, 2001)
This paper explores the emergence of the social work profession in Western Australia from beginnings in the 1920s through to 1970 when the first local graduates gained employment. The authors illustrate how WA's history both connects with and diverges from patterns of the profession's development in more populous states, througt, the use of interviews conducted with pioneering social workers These oral histories illuminate how gender, class and other markings of privilege and power framed, and were framed by, the education, practice, sites of practice and career paths of social workers in the early years. Two interacting themes identified in this research were restricted employment possibilities for social workers in the State and a lack of locally available professional education until the mining boom of the sixties. The paper concludes by listing six lessons for current practitioners: the transcendent importance of reading contexts; identifying and developing relevant sites of practice; maintaining flexible boundaries of professional practice; being able to articulate a dynamic value base to drive practice; the importance of practitioners in shaping education, and continuing practitioner reflexivity.